ANALISIS SPASIO-TEMPORAL KEJADIAN BANJIR DI KOTA PALEMBANG TAHUN 2024 - 2026 - R A S Delima Amanda Putri; Verinazul Septriansyah; Marice Agustini (LATERAL: Jurnal Teknik Sipil, 2026)
Urban flooding is a recurrent hydrometeorological disaster in Palembang, primarily caused by high-intensity rainfall, limited drainage capacity, and rapid urbanization. The spatio-temporal patterns identified in this study indicate a tendency for recurrent flood events to occur in the same locations, providing a basis for determining priority zones for urban flood vulnerability assessment and mitigation planning. This study analyzes 13 flood events recorded between 2024 and 2026 using data obtained from the Disaster Information System (SITABA) managed by the Ministry of Public Works of the Republic of Indonesia. The analyzed data include geographic coordinates, occurrence dates, flood causes, inundation depths, and impacts on infrastructure. Spatial analysis reveals that flood-prone areas are concentrated in the districts of Ilir Timur I, Ilir Timur II, Ilir Barat I, Seberang Ulu I, and Kemuning, which are characterized by extensive impervious surfaces and inadequate drainage systems. Temporal analysis indicates an increasing frequency of flood events, with inundation depths ranging from 10 to 80 cm. The primary causes of flooding were identified as high-intensity rainfall exceeding drainage system capacity, compounded by backwater effects from the Musi River. These findings provide important insights for urban flood mitigation planning, drainage system rehabilitation, and the development of more resilient urban water management strategies in Palembang City.